Weighted compromise trees: a method to summarize competing phylogenetic hypotheses. (9th October 2012) - Sharkey, Michael J.; Stoelb, Stephanie; Miranda‐Esquivel, Daniel R.; Sharanowski, Barabara J.
Abstract A new consensus method for summarizing competing phylogenetic hypotheses, weighted compromise, is described. The method corrects for a bias inherent in majority‐rule consensus/compromise trees when the source trees exhibit non‐independence due to ambiguity in terminal clades. Suggestions are given for its employment in parsimony analyses and tree resampling strategies such as bootstrapping and jackknifing. An R function is described that can be used with the programming language R to produce the consensus.